Time in teams: cognitions, conflict and team satisfaction - Standifer, R. L.; Raes, A. M. L.; Peus, C.; Passos, A. M.; Santos, C. M.; Weisweiler, S. (Journal of Managerial Psychology, 2015)
Purpose – The purpose of this paper is to provide more insight into team temporal constructs and team satisfaction, this study proposes and tests a multiple mediation model of shared temporal cognition (STC), temporal conflict (TC), action processes, and team satisfaction. Design/methodology/approach – The authors test the theoretical model in a sample of 364 student teams (1,414 individuals) from universities in the USA, Switzerland, Germany, and Portugal. Participants completed questionnaires at three points in time. Findings – Results indicated a direct, positive relationship between STC and team satisfaction and a direct, negative relationship between TC and team satisfaction. Action processes and TC partially and sequentially mediated the relationship between STC and team satisfaction over time. Research limitations/implications – This study was restricted to self-report, to a student population, and to Western cultures. The study was not of an experimental nature which prevents making causal claims regarding relationships among variables. Practical implications – These results demonstrate the need for teams to be conscious of time and its relationship to team interaction and satisfaction. The authors advise both team leaders and members to acknowledge the importance of STC. Social implications – The need for temporal awareness and STC in collaborative endeavors, and the need to mindfully utilize action processes to minimize conflict and assist in the effective use of shared cognition is widely applicable from a societal perspective. Originality/value – This study provides new theoretical and empirical insight into a multiple mediation model including STC, TC, action processes, and team satisfaction. The size and multi-cultural nature of the sample also enhance the generalizability of the findings.